Vector‐Borne Diseases and Climate Change: A Community Health Nursing Perspective Using an Umbrella Review. - Soleimanpour, Samira; Moslehi, Shandiz; Dowlati, Mohsen; Tavan, Asghar; Narimani, Sajjad (Public Health Nursing)
Background: Climate change is intensifying the spread of vector‐borne diseases through rising temperatures, changing rainfall patterns, and the potential release of ancient pathogens from melting polar ice. Community health nurses (CHNs) play a vital role in helping communities adapt to these evolving health threats. This study aims to synthesize evidence on the link between climate change and vector‐borne disease outbreaks and to propose a theoretical framework, the Climate Change Adaptation Theory (CCAT), that supports CHNs in leading community adaptation strategies. Methods: An umbrella review was conducted by systematically searching PubMed, Scopus, Web of Science, and Embase databases for relevant systematic review articles. Selected studies were analyzed to identify key themes related to vector‐borne diseases and climate change. Results: Of the total 2420 retrieved articles, 44 reviews were received, of which, after reviewing the full text of the articles, 18 articles met the inclusion criteria. Four main concepts were identified in the reviews around climate change: human activities facilitating disease emergence; global warming and the El Niño phenomenon; melting polar ice caps and pandemic risk; and the critical role of CHNs in climate change adaptation. Conclusion: CCAT integrates existing health education models and highlights the leadership role of CHNs in effectively educating communities on climate change adaptation, thus mitigating risks associated with vector‐borne diseases.